Deskripsi Gejala dan Tingkat Serangan Penyakit Busuk Hitam Pada Batang Tanaman Buah Naga Merah (Hylocereus polyrhizus, L.) di Padang Pariaman, Sumatera Barat - Resti Helvetia; Nasril Nasir; - Jumjunidang (Universitas Andalas, 2013)
Red dragon fruit Hylocereus polyrhizus is the fruit with a high value in industry. However, since the past two years, the fruit is being attacked by some pathogens and cause severe disease in West Sumatra. One of the diseases is black rot disease. The purpose of the research was to characterize the symptoms and disease severity of the black disease stem rot on red dragon fruit. The research was conducted from December 2012 until February 2013 and was taken place at Solok Tropical Fruit Research Institute and Microbiology laboratory of Biology Department Faculty of Mathematic and Natural Science, Andalas University, Padang, West Sumatera. This study was using direct observation method and the data were analyzed descriptively. The result showed that the percentage of the black disease of stem rot of dragon fruit was 47.3 % while disease severity index of it was 1.22. The isolated pathogen on the black disease stem rot of dragon fruit were Fusarium sp. and Xanthomonas sp.Keywords: Dragon fruit, black rot disease, disease severity